2010
DOI: 10.15288/jsad.2010.71.219
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adolescent Exposure to Intimate Partner Violence on Substance Use in Early Adulthood

Abstract: ABSTRACT. Objective: Youth exposure to intimate partner violence has been theorized to increase the risk of adverse outcomes in adulthood including substance-use problems. However, the limited research on the association between early exposure to intimate partner violence and later alcohol-or drug-use problems is inconclusive. Using a prospective design, this study investigates whether adolescent exposure to intimate partner violence increases the risk for problem substance use in early adulthood and whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 74 publications
0
36
0
Order By: Relevance
“…The male-female differences in the relationship between substance use and adverse events appear to differ by event type. 1517 For instance, while the associations between substance use and both interpersonal (e.g., breakdown of friendships) and violence events (e.g., victim of violence) tend to be stronger for female than male adolescents, 16, 17 the reverse appears to be true for instability/transition events (e.g., eviction) as they were positively associated with substance use among males and not females. 15 However, none of the above studies included gambling as part of a battery of addictive behaviors.…”
Section: Introductionmentioning
confidence: 97%
“…The male-female differences in the relationship between substance use and adverse events appear to differ by event type. 1517 For instance, while the associations between substance use and both interpersonal (e.g., breakdown of friendships) and violence events (e.g., victim of violence) tend to be stronger for female than male adolescents, 16, 17 the reverse appears to be true for instability/transition events (e.g., eviction) as they were positively associated with substance use among males and not females. 15 However, none of the above studies included gambling as part of a battery of addictive behaviors.…”
Section: Introductionmentioning
confidence: 97%
“…In general population, have been reported prevalences of abuse range between 6.2 and 33% (Finkelhor, 1994;Kendler et al, 2000;Lampe, 2002;Dube et al, 2003;Min et al, 2007;Pereda and Forns, 2007;Smith et al, 2010;Young-Wolff et al, 2011;Finkelhor et al, 2014). In substance-dependent patients samples, the prevalences found are higher than in general population, from 16 to 73% (Medrano et al, 1999;Hyman et al, 2007;Chermack et al, 2008;Douglas et al, 2010;Walton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Women who have experienced intimate partner violence (Smith et al, 2010) and physical abuse in childhood (Lansford et al, 2010) have higher risk of developing an addiction than male victims of the same experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Substance Abuse : Although some studies found the association between child exposure to domestic abuse and later substance abuse problems to be muted (Smith, Elwyn, Ireland, & Thornberry, 2010 ), mostly there seems to be a consensus that children who suffered physical and sexual abuse, witnessed violence, and who have family members with substance use issues themselves, are at increased risk for substance abuse that appear to be moderated by the concurrent presence of PTSD symptoms (Kilpatrick et al, 2000 ). Similarly, parental substance abuse directly and signifi cantly increased the prevalence of child abuse, by about 1.4:1, while experiencing or witnessing violence increased adolescent substance abuse by a factor of about two (Kilpatrick et al, 2000 ).…”
Section: Trauma Genetics and Substance Abusementioning
confidence: 99%